The role of cardiac lymphatic dysfunction in the progression of myocarditis - Kurup, Shreya; Hu, Daniel A.; Kume, Tsutomu (Frontiers in Cardiovascular Medicine, 2025)
Myocarditis, an inflammatory disease of the heart muscle, is a leading cause of sudden cardiac death in young adults and a major contributor to the development of dilated cardiomyopathy. Many studies highlight immune-mediated cardiomyocyte injury as a major contributor to myocarditis progression; however, myocardial edema may also play a significant role that has been overlooked. Beyond being a passive byproduct of inflammation, edema can mechanically stress the myocardium and create a proinflammatory microenvironment that may stimulate fibrosis, stiffen the myocardium, and impair cardiac function. Myocardial edema arises from an imbalance between vascular filtration and lymphatic clearance, often triggered by disrupted endothelial junctions that increase vascular permeability. The resulting accumulation of interstitial fluid fosters sustained inflammation, fibroblast activation, and extracellular matrix (ECM) remodeling. Furthermore, recent research highlights the therapeutic potential of targeting lymphatic regeneration to enhance edema resolution, attenuate inflammation, and limit fibrotic remodeling. This review examines the mechanistic pathways by which lymphatic dysfunction in myocarditis impairs lymphatic fluid clearance, focusing on the breakdown of lymphatic integrity, cytokine-mediated suppression of lymphangiogenesis, and maladaptive lymphatic remodeling. These processes contribute to adverse ventricular remodeling and dysfunction. Given that myocardial edema may be a key mediator for these pathological changes, we also discuss how emerging imaging techniques such as cardiac magnetic resonance (CMR) have enhanced the ability to detect and quantify edema, reinforcing its clinical relevance as both a diagnostic marker and prognostic indicator in myocarditis. Understanding the mechanistic pathways linking myocardial edema to pathology in myocarditis is promising for identifying novel therapeutic interventions.